The Promotion of Mangrove Ecotourism through Social Networking in Mempawah Regency - Destiani, Putri; Dolorosa, Eva; Kurniati, Dewi (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Mangrove Ecotourism was a tourist attraction that had potential in Mempawah Regency. Ecotourism Mempawah Mangrove Park and Polaria Tanjung Pagar were tourist attractions that prioritize the aspects of nature conservation, education as well as natural beauty of mangrove forests. Tourists at Mempawah Mangrove Park and Polaria Tanjung Pagar tended to experience fluctuation. This indicated the lack of promotional activities performed, especially promotion on social networking. The research aims were to formulate criteria and alternatives for promotional activities through social networking in increasing tourist visits. The research method that used was a descriptive quantitative survey method using the Analytical Hierarchy Process (AHP) with Expert Choice 11 software. There were 60 research respondents who were taken by purposive sampling by distributing the e-questionaire link via google form. The results showed that the main priority for the alternative Instagram and Facebook accounts at Mempawah Mangrove Park and Polaria Tanjung Pagar was context strategy. Ecotourism Mempawah Mangrove Park and Polaria Tanjung Pagar needed to prioritize alternative context strategies in providing promotional activities on social networking such as increasing the presentation of informative information and conducting training or providing comparative studies for employees to other ecotourisms to increase employee knowledge and skills.